Efeito do ácido abscísico nas bombas de prótons vacuolares e enzimas antioxidantes em Vigna unguiculata (L.) Walp - Rebouças, Deborah Moura (2011)
Abscisic acid (ABA) is a phytohormone that plays critical roles in regulating plant responses to growth and development. The vacuole of higher plants is an organelle that occupies a larger part of the cell. The acidic condition is maintained by two distinct proton pumps, VATPase and V-PPase. It is known these proton pumps play essential roles in plant responses to environmental changes. The electrochemical gradient promoted by these enzymes is the driving force for the accumulation of ions and other solutes in the vacuole, being important to maintain cytosolic ion homeostasis and cellular metabolism. Antioxidant enzymes constitute a defense system against reactive oxygen species, which can cause damage to plant development. The aim of this study was to study the effect of the abscisic acid in the growth and physiological parameters, as well as the effect on vacuolar proton pumps and antioxidant enzymes (SOD, CAT and APX) from Vigna unguiculata cv. Pitiuba. The seeds of V. unguiculata were germinated in sand and grown for 15 days, with application of Hoagland solution in the absence (control) or presence of 0.1 µM ABA in the third, seventh and tenth days after germination.The effects of the abscisic acid (ABA) on the growth, stomatal conductance, transpiration, photosynthesis, internal CO2 concentration, V-ATPase subunit A and V-PPase activities and expression and antioxidant enzymes activities of Vigna unguiculata were analyzed. ABA increased the plants growth but did not affect the physiological parameters; induced an increase on V-ATPase hidrolytyc activity in leaves and on V-PPase in roots; ABA increased the transcripts of VuVHA-A and VuVHP in leaves and decreased the VuVHA-A transcripts in roots; caused increase in the leaves and roots catalase activity. These results suggest that the abscisic acid regulate the activity and the genes expression of the vacuolar proton pumps, as well as the antioxidant enzymes activity, being thus important effectors that regulate the development of V. unguiculata plants.